An empirical study about the capital requirements and banks' behavior of selected commercial banks in the Philippines from 2007-2013 - Berrir, Abigail B. (Animo Repository, 2012)
The study examines the association between the capital regulations and bank's behavior of selected commercial banks in the Philippines. The period covered in this study was from 2007-2013. Also, it wants to answer the following problems: (1) What are the effects of the BSP's regulations on capital requirements on the following? (2) How do commercial banks respond to BSP's regulation which affects their capital adequacy? Both questions are in terms of capitalization and risk-taking. Regression analysis was used to analyze the data, specifically the method of three-stage-least-squares. The model used in the study was developed by Shrieves and Dahl (1992) and further specified by Rime (2000). Two variables were used in defining the capital, which is the ratio of capital to total assets (RCTA) and ratio of capital to risk-weighted assets (RCWA). On the other hand, risk was defined using the risk-weighted assets to total assets (RWA). The results showed that for RCTA, only the variables return on assets and change in risk has a positive and significant effect on capitalization. While for risk, size has a negative and significant effect, and change in capital has a positive and signifcant effect. Moreover, for RCWA, the results showed that for capitalization only return on assets has a positive and significant effect same for RCTA. On the other hand, the variables that are significant for risk are loan losses, which have a negative impact and risk-weighted assets from the previous year which has a positive impact.